The role of motivation in selection processes—comparing sports and business - Brinkmöller, Birte; Dreiskämper, Dennis; Höner, Oliver; Strauss, Bernd (Frontiers in Sports and Active Living, 2024)
Talent identification and selection in sports pose significant challenges, necessitating a nuanced understanding of factors influencing athletes’ elite-level potential. While physical and physiological aspects have conventionally played roles in the selection process, also other constructs of talent development have to be considered. Various talent models have included psychological aspects, especially motivation, as either moderators or catalysts. Based on empirical evidence of the relationship between motivation and performance, different views are hold in which form motivation should be used for talent selection. Considering the hierarchical model of achievement motivation and self-determination theory, the importance of different motivational dimensions in talent selection is assessed. This study extends its focus beyond sports, exploring whether differences and similarities between sports and business in their selection processes exist. The objective is to discern whether scouts, coaches and recruiters prioritize motivational dimensions differently. Along with the statistical analyses [conjoint analysis, analytical hierarchy processes (AHP) and constant-sum procedures], this research aims to provide insights into the weighted importance of diverse motivational dimensions and their influence on the decision-intention of decision-makers. The study aims to provide exploratory insights into how motivational dimensions could inform talent selection processes by comparing different contexts. This research may offer a first step to further investigate practical applications for talent identification and selection processes with insights from other contexts.